Inoperable Primary Ovarian Carcinoid Led to the Progression of Carcinoid Heart Disease From Right-Sided to Both-Sided Involvement. (January 2017) - Tadokoro, Tomonori; Katsuki, Shunsuke; Ito, Koji; Onitsuka, Ken; Nakashima, Atsuhiro; Sasaguri, Takakazu; Miyata, Kenji; Yamamoto, Hideo; Mohri, Masahiro
Abstract : Supplemental Digital Content is available in the text.